2013
DOI: 10.1002/jgrb.50121
|View full text |Cite
|
Sign up to set email alerts
|

Permanent upper plate deformation in western Myanmar during the great 1762 earthquake: Implications for neotectonic behavior of the northern Sunda megathrust

Abstract: The 1762 Arakan earthquake resulted from rupture of the northern Sunda megathrust and is one of those rare preinstrumental earthquakes for which early historical accounts document ground deformations. In order to obtain more comprehensive and detailed measurements of coseismic uplift, we conducted comprehensive field investigations and geochronological analyses of marine terraces on the two largest islands in western Myanmar. We confirm 3–4 m of coseismic coastal emergence along southwestern Cheduba Island, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(61 citation statements)
references
References 61 publications
7
52
1
Order By: Relevance
“…Melnick et al, 2009;Wang et al, 2013;Pedoja et al, 2013). These results are fundamental for seismic hazard assessment and mitigation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…Melnick et al, 2009;Wang et al, 2013;Pedoja et al, 2013). These results are fundamental for seismic hazard assessment and mitigation.…”
Section: Accepted Manuscriptmentioning
confidence: 86%
“…However, as Steckler et al (2008) point out, major events do occur in high-sediment-input systems such as the 1964 Alaskan earthquake (Ruff 1989(Ruff , 1992, and the high geothermal gradients associated with thick sediment piles may actually promote stick-slip behaviour at relatively shallow depths. Wang et al (2013) confirmed that slip did occur on the megathrust interface on the Arakan segment beneath the offshore extension of the Ganges-Brahmaputra delta in the Bay of Bengal, suggesting this sediment-clogged system is capable of failure. The fact that slip in the Arakan earthquake appears to have been transferred from the megathrust onto imbricate faults within the accretionary prism (Wang et al 2013) supports the suggestion that severe damage was not reported in western cities such as Dhaka after the 1548 earthquake, due to a similar process (Steckler et al 2008).…”
Section: Geodesymentioning
confidence: 65%
“…Wang et al (2013) confirmed that slip did occur on the megathrust interface on the Arakan segment beneath the offshore extension of the Ganges-Brahmaputra delta in the Bay of Bengal, suggesting this sediment-clogged system is capable of failure. The fact that slip in the Arakan earthquake appears to have been transferred from the megathrust onto imbricate faults within the accretionary prism (Wang et al 2013) supports the suggestion that severe damage was not reported in western cities such as Dhaka after the 1548 earthquake, due to a similar process (Steckler et al 2008). Steckler et al (2008) suggest that this behaviour may occur because the burial of the tip of the accretionary prism beneath the sediments of the Ganges-Brahmaputra delta promoted the transfer of megathrust slip onto imbricate thrusts to thicken the deforming wedge.…”
Section: Geodesymentioning
confidence: 65%
See 1 more Smart Citation
“…Particularly notable earthquakes occurred in A.D. 1762 and 1897. The A.D. 1762 Arakan earthquake occurred off the east coast of Bangladesh, which Wang et al (2013) estimated had a magnitude of ~8.5 Mw (moment magnitude). This event caused widespread heavy damage, liquefaction and landslides in the Chittagong region, and a rapid increase in the level of the river at Dhaka that drove hundreds of boats onshore and caused signifi cant loss of life (Martin and Szeliga, 2010).…”
Section: Earthquakes In Bangladeshmentioning
confidence: 99%